2021
DOI: 10.3390/su13094899
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening the Role of Academic Institutions and Innovation Brokers in Agri-Food Innovation: Towards Hybridisation in Cross-Border Cooperation

Abstract: Existing research suggests that regions can develop their long-term competitive advantage through well-functioning interregional innovation cooperation. In this article, we use the example of innovation in small and medium-sized agri-food enterprises (SMEs) to scrutinise and compare regional innovation approaches on each side of the Dutch-German border and explore how they can converge into a cross-border innovation space. Particular attention is paid to the role of academic institutions and innovation brokers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 64 publications
1
10
0
Order By: Relevance
“…An analysis of the reasons that lead cooperatives to adopt cross‐border models reveals that they are similar to those driven by changes in the industry which force large companies to go international (Nilsson & Madsen, 2007). Thus, one of the major benefits of these processes for cooperatives is the chance to take advantage of different skills and alternative ways of looking at things in different regions (Knickel et al., 2021).…”
Section: Conceptual and Regulatory Frameworkmentioning
confidence: 99%
“…An analysis of the reasons that lead cooperatives to adopt cross‐border models reveals that they are similar to those driven by changes in the industry which force large companies to go international (Nilsson & Madsen, 2007). Thus, one of the major benefits of these processes for cooperatives is the chance to take advantage of different skills and alternative ways of looking at things in different regions (Knickel et al., 2021).…”
Section: Conceptual and Regulatory Frameworkmentioning
confidence: 99%
“…However, it is not only joint innovation that contributes to the cooperation of neighboring countries. The potential for cooperation of neighboring countries in the field of innovation is determined by the costs of R&D, expertise, development, and technological innovation at the core of contemporary European problems, such as R&D in the field of renewable energy, an innovative infrastructure [37].…”
Section: Development Of a Theoretical Modelmentioning
confidence: 99%
“…Recent studies have suggested that collaborative development of agri-food innovations is at the core of sustainable cross-border cooperation, with an increasing role for academic institutions and innovative brokers [37].…”
Section: Development Of a Theoretical Modelmentioning
confidence: 99%
“…The impact of innovation can also be perceived from the perspective of the innovation ecosystem. Within this concept, knowledge and technology are created, disseminated, and used through the interaction of geographically-close actors and their relations, including organizations, companies, research centers, and policymakers [69], as the geographical proximity of innovation actors supports the exchange of tacit knowledge [70]. Cluster initiatives are often these intermediaries that support innovation in geographical proximity [71].…”
Section: Internationalization Of the High Tech Industry As An Entrepreneurial Ecosystem Shaping The Start-up Processmentioning
confidence: 99%